ANALISI PENGETAHUAN, PERILAKU DAN DUKUNGAN PEMERINTAH TERHADAP PENGELOLAAN SAMPAH DI KABUPATEN LABUHANBATU UTARA - Rahman Al Faris; Hamdani Harahap; Hesti Wahyuningsih (Program Pascasarjana Universitas Riau, 2022)
This study aims to analyze the effect of knowledge, behavior, and government support on waste management in Labuhanbatu Utara. This study uses research methods to analyze numerical dataprocessed by statistics. This study tries to see the relationship between exogenous variables (X), namely knowledge (X1), behavior (X2), and government support (X3) on endogenous variables (Y), namely waste management. The population in this study is thosin the area of TPA waste management. The population selected is the people of Wonosari Village, Kualuh Hulu District and Damuli Kebun Village, Kualuh Selatan District. The study's results show its effect on waste management in Labuhanbatu Utara Regency. Behavior affects waste management in Labuhanbatu Utara Regency. Good or bad behavior owned by the community, especially regarding waste, affects waste management. Government support does not affect waste management in Labuhanbatu Utara Regency. The support provided by the government could not improve waste management.